The tale of the shining princess - Fisher, Sally, 1939- (Caedmon, 1982)
Retells the ancient Japanese tale about a fairy princess who spends a number of years on earth enriching the life of a simple bamboo cutter, winning the hearts of suitors, and enchanting the emperor.